Optimalisasi Penggunaan Batubara Kualitas Rendah (Lignite Coal) Pada Pembakaran Klinker yang Stabil dan Ekonomis di Industri Semen - Setiawan, Muhammad Fazar; Irawan, Chairul (Lambung Mangkurat University Press, 2024)
Coal is the main fuel used to make clinker in the cement industry. As time goes by the cost of purchasing coal is getting higher and supplies are running low, making it necessary to optimize to reduce production costs. To deal with this problem, high-quality coal is mixed with low-quality coal (lignite coal) using the Chevron method. The Chevron method is a method of stacking coal continuously along the pile axis and moving horizontally in a predetermined area. The coal is stacked in layers with layers of low-quality coal (lignite coal) and high-quality coal alternately according to the lignite coal mixture ratio. The specified ones are 30%, 40%, 50% and 60%. The optimum mixture ratio of low-quality coal (lignite coal) is 60%, which can reduce the cost of purchasing coal by IDR. 486,899 per ton. Daily consumption of coal for burning clinker is around 1000 tons per day so the efficiency of coal purchasing costs reaches around 14.6 billion rupiah per month while maintaining the quality of the clinker produced with a free CaO range of 1.04 – 1.40%, below the Indonesian National Standard (SNI ) namely 1.50%.